Given
S = 1 + 2 2 2 − 1 + 1 2 3 − 2 2 + 2 4 2 5 2 − 7 + 8 0 1 7 − 1 2 2 + … ,
find ⌈ S ⌉ .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Awesome! I just got that.
Can you explain how ( 2 − 1 ) 4 = 1 7 − 2 2 ?
Oh sorry sir for the third and fourth term i was getting a nice hint so for the next term i copied the trem from the question. Edited , if my approach is not correct then what we can do?
if the fourth term has 2 instead of 12 , then the sequence is not followed by the fourth term , now till infinity the expression reachs , then every term should follow the sequence , i think so also here it is written enhance your concepts on p r o g r e s s i o n s , thus there would be a common ratio(constant increase in every term) so it should'nt be flagged
Thank you
@Vraj Mehta Can you clarify what the fifth term is? Should the numerator be 1 7 − 1 2 2 ?
@Calvin Lin – You are Right!Calvin Lin Sorry But Cant change ..Solve the ques Assuming the Fifth Term is 17-12*root2.
@Vraj Mehta – Thanks for clarifying. I have updated the problem accordingly.
Note that you can edit your problem directly by selecting "edit" from the "dot dot dot" menu in the lower right corner.
Thank you..Megh Choksi
Problem Loading...
Note Loading...
Set Loading...
We can see here that ❤ ❤ ( 2 − 1 ) 2 = 3 − 2 2 , ( 2 − 1 ) 3 = 5 2 − 7 , ( 2 − 1 ) 4 = 1 7 − 1 2 2 . .
Let 2 2 − 1 = x
Thus,
S = 1 + 2 x + 6 x 2 + 1 2 x 3 . . . . . . . .
S = 1 + 1 × 2 x + 2 × 3 x 2 + 3 × 4 x 3 . . . . . . . . . . . . . . . .
S = 1 + ( 1 − 2 1 ) x + ( 2 1 − 3 1 ) x 2 + ( 3 1 − 4 1 ) x 3 + . . . . . . . . . . . . . .
S = ( 1 + x + 2 x 2 + 3 x 3 + . . . . . ) − ( 2 x + 3 x 2 + 4 x 3 + . . . .
S = 1 − l o g ( 1 − x ) − x 1 ( 2 x 2 + 3 x 3 + . . . . . . . . . )
S = 1 − l o g ( 1 − x ) − x 1 ( − l o g ( 1 − x ) − x )
S = 2 − 2 1 ( 2 + 1 ) l o g 2
S = 1 . 1 6 3 3
[ S ] = 1
@Vraj Mehta Nice question! ♡ ♡ ♡ ♡ ❤ ❤ ❤ ❤